Explorative study for the structural elements of Mimar Sinan mosques: an evaluation with k-means clustering algorithm - Çalışkan, Ekrem Bahadır; Karakuş, Filiz (Cultural Heritage and Science, 2024)
Mimar Sinan, who served as master architect for nearly fifty years in the 16th century, when the Ottoman Empire was at its strongest, designed landmark buildings that left their mark on the city identities within the empire's borders. The subject of this study is to evaluate the mosques designed by Mimar Sinan, the most well-known architect of the 16th-century Islamic Region, in the capital, Istanbul, and other cities. The structural components and features of 44 mosques designed/built by Mimar Sinan (dome diameter, height of the dome from the ground, width/height dimensions, number of minarets and minaret balconies, location, top covering elements (domes, half domes, small domes, quarter domes), number of load-bearing elements, transition elements to the dome and their numbers) were analyzed in order to identify and discuss possible relationships and patterns between them. Since the number of studies evaluating and exploring structural system properties of Mimar Sinan mosques is very few, this study is very important in terms of the contribution to the existing literature. The data from the literature review are searched with the K-means clustering algorithm, a machine learning method, and the relationships and patterns between them are revealed. The results are converted into definitions of variables for discussion and evaluation.